Gen-Z Perspective on Exogamy Marriage in Tanjungbalai - Zuhana Syahfitri Siregar; Alemina Br. Perangin-angin (Departement of Mathematics Education, 2023)
Gen-Z are familiar with early marriage or often called “Nikah Muda” in Indonesia.It is also related to Gen-Z who are concerned with Exogamy Marriage in Tanjungbalai. There are so many pros and cons point of view from Gen-z about exogamy itself. Modernization is one of the impact of Gen-Z perspective of exogamy.This aricle aims to observe Gen-Z perspective on exogamy marriage spesifically in the region of Tanjungbalai. The paricipants are the members of HIKMAT (Himpunan Mahasiswa Tanjunngbalai). There are 10 participants with the age 22-26 years old.This article conducted by using interview and observation method . The result of this article will be useful as a representative opinion from Gen-Z and it may change the other people perspective about Exogamy itself in order to respect the people’s choice for their own marriage.